2018
DOI: 10.1093/humrep/dey028
|View full text |Cite
|
Sign up to set email alerts
|

Origin and composition of cell-free DNA in spent medium from human embryo culture during preimplantation development

Abstract: This work was funded by Igenomix S.L. There are no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 21 publications
4
110
0
Order By: Relevance
“…Many studies focused on cell‐free DNA recovered from blastocoel fluid with controversial data regarding the concordance rate with TE cells . Recently, cell‐free DNA has also been detected in blastocyst‐spent culture media but no agreement on concordance rate with the genetic status of embryos has been found . Although both strategies appear to be attractive methods, they are characterized by some limitations including the incomplete representation of the whole embryonic genome, the potential maternal DNA contamination, the poor nucleic acid integrity and the unknown sampling time points to obtain acceptable amplification rates .…”
Section: Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies focused on cell‐free DNA recovered from blastocoel fluid with controversial data regarding the concordance rate with TE cells . Recently, cell‐free DNA has also been detected in blastocyst‐spent culture media but no agreement on concordance rate with the genetic status of embryos has been found . Although both strategies appear to be attractive methods, they are characterized by some limitations including the incomplete representation of the whole embryonic genome, the potential maternal DNA contamination, the poor nucleic acid integrity and the unknown sampling time points to obtain acceptable amplification rates .…”
Section: Threatsmentioning
confidence: 99%
“…[66][67][68][69] Recently, cell-free DNA has also been detected in blastocyst-spent culture media but no agreement on concordance rate with the genetic status of embryos has been found. [70][71][72][73][74] Although both strategies appear to be attractive methods, they are characterized by some limitations including the incomplete representation of the whole embryonic genome, the potential maternal DNA contamination, the poor nucleic acid integrity and the unknown sampling time points to obtain acceptable amplification rates. 75 Well-designed studies are needed to evaluate the efficacy of cell-free DNA employment on clinical outcomes.…”
Section: Invasive and No Standardized Proceduresmentioning
confidence: 99%
“…[16][17][18] Despite greater accuracy with cf-DNA from spent culture media (SCM) after day 5 than after day 3, the ploidy concordance rate of cf-DNA of SCM compared with that of trophectoderm biopsy is limited, reported as 65% by Ho et al 19 and 84% by Xu et al 20 It is possible that maternal contamination from the cumulus complex cells and mosaicism might contribute to diagnostic inaccuracy. 19,21 More promisingly, comparison between cf-DNA from blastocoel fluid (BF) aspirated from blastocysts and trophectoderm biopsy reveals a very high ploidy concordance of 97%, 22 although other groups have not reported such high figures. In many instances, BF removal is a routine step performed to reduce the risk of crystal formation for blastocyst cryopreservation, and appears to have no detrimental effect.…”
Section: New Technologiesmentioning
confidence: 99%
“…and 84% by Xu et al . It is possible that maternal contamination from the cumulus complex cells and mosaicism might contribute to diagnostic inaccuracy . More promisingly, comparison between cf‐DNA from blastocoel fluid (BF) aspirated from blastocysts and trophectoderm biopsy reveals a very high ploidy concordance of 97%, although other groups have not reported such high figures.…”
Section: Introductionmentioning
confidence: 99%
“…Not only is it important to optimize DNA amplification to obtain results from as many samples as possible, but it is also vitally important that the culture medium used is free of DNA contaminants and that genetic material from other external sources is avoided. In a previous study, Vera-Rodriguez et al (5) reported high levels of contamination of a maternal origin (presumably from cumulus cells) and predicted that only 8% of the genetic material in the SCM was embryonic. To mitigate the issue of maternal DNA contamination, several groups have advocated a two-step approach to embryo culture, wherein the embryo is transferred to a new drop of medium, usually on day 3.…”
mentioning
confidence: 99%